Detection of anti-arboviral immunoglobulin G by using a monoclonal antibody-based capture enzyme-linked immunosorbent assay - Johnson, A J; Martin, D A; Karabatsos, N; Roehrig, J T (Journal of clinical microbiology, 2000)
Monoclonal antibody (MAb)-based capture enzyme-linked immunosorbent assays (ELISAs) for the detection of anti-arboviral immunoglobulin G (IgG ELISAs) were developed for a comprehensive array of medically important arboviruses from the Alphavirus, Flavivirus, and Bunyavirus genera. Tests were optimized and standardized so that maximum homology could be maintained among working parameters for the different viral agents, enabling a wide range of viruses to be easily tested for at one time. MAbs were screened for suitability as capture vehicles for antigens from the three genera. The final test configuration utilized group-reactive MAbs eastern equine encephalitis virus 1A4B-6, dengue 2 virus 4G2, and La Crosse encephalitis virus 10G5.4 to capture the specific inactivated viral antigens. Serum IgG was detected by using alkaline phosphatase-conjugated anti-human IgG (Fc portion). A dilution of 1:400 was chosen as the universal screening serum dilution, with endpoint titrations of serum samples testing positive eliminating occasional false-positive results. IgG ELISA results correlated with those of the standard plaque-reduction neutralization assays. As expected, some test cross-reactivity was encountered within the individual genera, and tests were interpreted within the context of these reactions. The tests were standardized for laboratory diagnosis of arboviral infections, with the intent that they be used in tandem with the corresponding IgM antibody-capture ELISAs.